Effects of tidal variations on total nitrogen concentration, speciation, and exchange flux in the Shuidong Bay coastal water, South China Sea - Zhang, Peng; Luo, Weisheng; Fu, Miaojian; Zhang, Jibiao; Cheng, Mingyue; Xie, Jiale (Frontiers in Marine Science, 2022)
Nitrogen (N) plays an important role in marine ecosystems as a biogenic element for phytoplankton. The tidal cycle had major influence on various biogeochemical parameters of the bay and changed nutrients input with the ebb and flow of the tide. In this study, we collected samples from Shuidong Bay (SDB) in China, in August 2021, to explore the periodic variations in coastal waters during spring and neap tides. The effects of spring and neap tides on different speciation of nitrogen in the SDB and the exchange fluxes between the SDB and the South China Sea (SCS) were investigated. The results indicated that the concentrations of particulate nitrogen (PN) and N-NO2- were significantly different between the spring and neap tides (P < 0.05). The total nitrogen (TN) concentrations in SDB during the spring and neap tides were 258.12 ± 89.49 μmol/L and 231.77 ± 56.86 μmol/L. During the spring and neap tides, total dissolved nitrogen (TDN) accounted for 54.1% and 52.2% of TN, respectively. In addition, dissolved organic nitrogen (DON) accounted for 81.4% and 69.9% of the TDN during the spring and neap tides, respectively. Furthermore, the net exchange fluxes of different speciation of nitrogen showed that the net exchange fluxes of TN were transported from SDB to SCS during the spring and neap tide, with the net exchange fluxes of 37.7 t and 8.8 t, respectively. The net exchange flux of TN during spring tide was 4.3 times higher than that of neap tide. In addition, a significant negative correlation was observed between dissolved inorganic nitrogen (DIN) and salinity in SDB during the spring and neap tides (P < 0.001), indicated that DIN was mainly influenced by terrestrial sources inputs. A significant positive correlation (P < 0.01) was observed between PN and Chlorophyll-a in SDB during the spring and neap tides, implied that the assimilation of a large number of planktonic organisms promoted PN formation. The present results revealed that tidal variation played an important role in regulating N speciation and exchange flux in coastal waters, which had great implications for N biogeochemistry and water quality improvement in SDB.